2012
DOI: 10.1007/978-3-642-28108-2_19
|View full text |Cite
|
Sign up to set email alerts
|

Process Mining Manifesto

Abstract: Process mining techniques are able to extract knowledge from event logs commonly available in today’s information systems. These techniques provide new means to discover, monitor, and improve processes in a variety of application domains. There are two main drivers for the growing interest in process mining. On the one hand, more and more events are being recorded, thus, providing detailed information about the history of processes. On the other hand, there is a need to improve and support business processes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
431
0
26

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 763 publications
(502 citation statements)
references
References 2 publications
0
431
0
26
Order By: Relevance
“…The guiding principles and challenges were defined by an IEEE Task Force on Process Mining in the Process Mining Manifesto (2011) which aimed to "increase the maturity of process mining as a new tool to improve the (re)design, control and support of operational business processes" [13] (page 1). There are a range of process mining algorithms but most have problems when analysing event data from clinical workflows, either in failure to construct useful process models or in models which do not reflect reality, mainly because of incomplete and noisy input data [12].…”
Section: Process Mining In Oncologymentioning
confidence: 99%
“…The guiding principles and challenges were defined by an IEEE Task Force on Process Mining in the Process Mining Manifesto (2011) which aimed to "increase the maturity of process mining as a new tool to improve the (re)design, control and support of operational business processes" [13] (page 1). There are a range of process mining algorithms but most have problems when analysing event data from clinical workflows, either in failure to construct useful process models or in models which do not reflect reality, mainly because of incomplete and noisy input data [12].…”
Section: Process Mining In Oncologymentioning
confidence: 99%
“…The evaluation of the quality of event logs in process mining relies on trustworthiness (recorded events actually happened), completeness and well defined semantics [56]. These can be achieved by selecting pathways with required data points using the pathways framework.…”
Section: Knowledge Discovery Supportmentioning
confidence: 99%
“…The visualisation system allows for the close inspection and contextualisation of pathways, illustrating particular paths with similar features. It has been reported that a combination of visual analytics with automated process mining techniques would make possible the extraction of more novel insights from event data [56] and further work in this area is needed.…”
Section: Knowledge Discovery Supportmentioning
confidence: 99%
“…See [14] for logging guidelines and details on getting event data from databases using redo logs. It is apparent that a condition sine qua non for the application of process mining is the availability of faithful event logs, adhering to accepted standards (such as XES) and guaranteeing a certain quality level [15]. In many real-world settings, though, such event logs are not explicitly given, but are instead implicitly represented inside legacy information systems of organizations, which are typically managed through relational technology.…”
Section: Introductionmentioning
confidence: 99%